Studying The Advanced Pedagogical Views Of Abdulla Avlani - Akhrorova Zarina Azamatovna (Genius Journals, 2025)
This article examines the pedagogical views of Abdulla Avlani, an eminent figure in the field of education, who is known for his innovative and student-oriented approach to education. Avlani’s philosophy emphasizes personalized learning, critical thinking, creativity, and fostering a supportive learning environment. In this study, the main principles of Avlani’s pedagogical views and their impact on modern educational practice are studied
Keywords: Abdulla Avlani; pedagogical views; education